Carbon materials as new nanovehicles in hot-melt drug deposition - Bielicka, Agnieszka; Wisniewski, Marek; Terzyk, Artur; Gauden, Piotr; Furmaniak, Sylwester; Roszek, Katarzyna; Kowalczyk, Piotr; Bieniek, A (Institute of Physics Publishing Ltd., 2013)
The application of commercially available carbon materials (nanotubes and porous carbons) for the preparation of drug delivery systems is studied. We used two types of carbon nanotubes (CNT) and two activated carbons as potential materials in so-called hot-melt drug deposition (HMDD). The materials were first studied using Raman spectroscopy. Paracetamol was chosen as a model drug. The performed thermal analysis, kinetics, and adsorption–desorption studies revealed that nanoaggregates are formed between carbon nanotubes. In contrast, in pores of activated carbon we do not observe this process and the drug adsorption phenomenon mechanism is simply the filling of small pores. The formation of nanoaggregates was confirmed by the results of GCMC (grand canonical Monte Carlo) simulations and the study of the surface area on nitrogen adsorption–desorption isotherms. The application of carbon nanotubes in HMDD offers the possibility of controlling the rate of drug delivery. Performed MTT tests of nanotubes and drug-loaded nanotubes show that the observed decrease in cell viability number is caused by the influence of the cytostatic properties of nanotubes—they inhibit the proliferation of cells. The carbon nanotubes studied in this paper are essentially nontoxic.